Hubungan Pengetahuan Orang Tua, Personal Hygiene Dan Sanitasi Lingkungan Dengan Kejadian Kecacingan Pada Anak SD Negeri 94 Kendari Kecamatan Nambo Kota Kendari Tahun 2023 - Siti Nurwahida; Jafriati Jafriati; Siti Nurfadilah H (Lembaga Pengembangan Kinerja Dosen, 2024)
Helminths is a term that refers to a group of parasitic diseases caused by nematodes that are transmitted to humans through soil contaminated with feces. The incidence of worms is influenced by several factors, including poor environmental sanitation and personal hygiene, such as lack of cleanliness in washing hands, not wearing footwear, not paying attention to clean nails, and poor sanitation are factors that cause worm infections. In an effort to control worms, the Minister of Health has established regulations for the mass administration of worm prevention medication, hereinafter referred to as POPM worms. The general aim of this research is to determine the relationship between parental knowledge, personal hygiene and environmental sanitation with the incidence of worms in children at SD Negeri 94 Kendari in 2023. The population in this study is all active students at SD Negeri 94 Kendari in 2023. The results of this research show There is no relationship between parental knowledge and the incidence of worms with a P-value of 0.207, for personal hygiene it has a significant relationship with the incidence of worms with a P-value of 0.010 and for environmental sanitation it also has a significant relationship with the incidence of worms with a P-value 0.001.